EFFECT OF CUCUMBER (CUCUMIS SATIVUS) JUICE ON LOWERING BLOOD PRESSURE IN ELDERLY - Sumirah Budi Pertami; Dian Yuniar Syanti Rahayu; Budiono Budiono (Public Health of Indonesia)
Background: Hypertension is one of the diseases that cause high morbidity. The use of modern hypertension medical treatment may cause a side effect, so cucumber as one of traditional medicines may become a choice.